Influence of acid and alkali pre-treatments on thermal degradation behaviour of polyisocyanurate foam and its carbon morphology. (July 2017) - Xu, Jie; Wu, Tao; Peng, Chuang; Adegbite, Stephen
Abstract: The thermal degradation of polyisocyanurate foam samples were studied by TG/DTA, FTIR, and SEM. All samples with different isocyanate index (NCO/OH = 100, 200, 300) were pre-treated by H2 SO4, K2 CO3, and NaOH before heating. The measurements of DTG and DTA presented corresponding variability for different acidic and alkaline treatments. The activation energy of thermal decomposition was calculated based on kinetic reaction evaluation. The pronounced polyol and isocyanate regenerations were observed over degradation. Further FTIR measurements at elevated temperatures suggested the possibility of acidic hydrogen bonding catalyzation and alkaline reversible amide regeneration during degradation by chemical treatments. The morphology and growth mechanism of localized corrosion and microcrystallization were characterized based on SEM micrographs.